2016
DOI: 10.1186/s13046-016-0394-z
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the JNK-c-Jun pathway in response to irradiation facilitates Fas ligand secretion in hepatoma cells and increases hepatocyte injury

Abstract: BackgroundIt is well established that some irradiated liver non-parenchymal cells secrete pro-inflammatory cytokines to facilitate the development of radiation-induced liver disease. However, little is known on whether the irradiated hepatoma cells-mediated non-irradiated hepatocyte injury occurs in HCC patients. Here, we elucidated the roles of the irradiated hepatoma cells in driving non-irradiated hepatocyte injury and its underlying mechanism.MethodsSMMC7721 cells were cultured and divided into irradiated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 40 publications
3
29
0
Order By: Relevance
“…The transcription factor c‐jun, a component of AP‐1, is involved in the regulation of apoptosis and plays a vital role both in the extrinsic and intrinsic apoptotic pathways. The extrinsic pathway involves the interaction of death receptors with their ligands, and a recent report suggested that activation of c‐jun plays an important role in FasL expression . Our results show that knocking down JUN or treating cells with JNKi downregulates Fas/FasL and eliminates the proapoptotic effect of knocking down LRRN1.…”
Section: Discussionsupporting
confidence: 64%
“…The transcription factor c‐jun, a component of AP‐1, is involved in the regulation of apoptosis and plays a vital role both in the extrinsic and intrinsic apoptotic pathways. The extrinsic pathway involves the interaction of death receptors with their ligands, and a recent report suggested that activation of c‐jun plays an important role in FasL expression . Our results show that knocking down JUN or treating cells with JNKi downregulates Fas/FasL and eliminates the proapoptotic effect of knocking down LRRN1.…”
Section: Discussionsupporting
confidence: 64%
“…Furthermore, it has been suggested that several transcription factors, such as c‐Myc, nuclear factor (NF)‐kB, and activating protein (AP)‐1, are involved in regulation of FasL expression. While AP‐1 is a heterodimeric transcription factor composed of the subunits Jun and Fos and activated JNK phosphorylates the transcription factor c‐Jun, which results in increased AP‐1 transcription . Importantly, a c‐Jun‐ATF‐2‐like binding site was defined in the Fas‐L promoter which mediates transcriptional activation of Fas‐L and apoptosis in lymphocytes upon overexpression of MEKK1 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent report suggested that activation of the JNK-c-Jun pathway plays an important role in FasL expression. 19 Our previous study indicated that both ERK and JNK MAPKs are linked to activation of c-Jun by triggering its nuclear translocation in leukemia cells. 20 We therefore determined the effect of luteolin on the nuclear accumula-…”
Section: Nuclear C-jun Is Involved In Luteolin-induced Fasl Expressmentioning
confidence: 99%
“…Using bioinformatic analyses, we found that both miR-19b-3p and TNFAIP3 have a common apoptotic pathway—the NF-κB signaling pathway. Ionizing radiation is known to cause DNA DSBs and leads to lethal injury [9, 28]. IR-induced DSBs trigger a DNA damage response with NF-κB activation as the antiapoptotic factor in most cell types [2932].…”
Section: Discussionmentioning
confidence: 99%